Hyperfine-resolved spectrum of the molecular dication DCl2+ - Abusen, R; Bennett, F; Cox, S; McNab, I; Sharp, D; Shiell, R; Smith, F; Walley, J (2000)
We have obtained hyperfine-resolved infrared spectra of a PQ23(N) branch line in the v = 2-1 band of the X 3Σ- state of the molecular dication D35Cl2+. Analysis of the hyperfine structure allows us to estimate the magnitude of the Fermi contact interaction for the chlorine nucleus; bF(Cl) = 167 (25) MHz.